Word smart II : how to build a more educated vocabulary - Robinson, Adam, 1955-; Unrein, Judy; Curtin, Mariwyn; Princeton Review (Firm) (New York : Random House, 2006)
More than eight hundred additional words to help build an impressive vocabulary compiled by the staff of The Princeton Review will help anyone communicate more effectively and enhance the ability to take standardized tests.
At head of title: The Princeton Review.
"More words you need to know to : communicate effectively, be more persuasuive, get more from your reading, score higher on the SAT and other standardized tests"--Cover.
The revised 3rd edition of Word Smart II includes access to PrincetonReview.com.
Keywords: Vocabulary; English language -- Study and teaching; SAT (Educational test) -- Study guides